Halauxifen-Methyl+Diclosulam: New Option to Control Conyza spp. Prior Soybean Sowing - KRENCHINSKI,F.H. (2019)
ABSTRACT: Control of Conyza spp. prior to soybean sowing has faced difficulties because of the resistance cases in Brazil, hence new herbicides as halauxifen-methyl + diclosulam are important to manage this specie. The objective of this research was to evaluate the effectiveness of the herbicide halauxifen-methyl + diclosulam applied at pre-planting of soybean. The experiments were set up in three locations in Paraná State, Brazil, in the 2015/2016 season. The herbicide halauxifen-methyl + diclosulam was associated with glyphosate and compared to other commercial herbicide to Conyza spp. control. The application occurred 15 days before soybean sowing, in plants of Conyza spp. with an average height of 20-35 cm in the three areas. None of the treatments promoted Conyza spp. control above 90%, when soybean was at the V1 stage; however, the findings showed that halauxifen-methyl + diclosulam promoted better control in comparison to the other treatments. The control reached >90% at V3 soybean development stage, in which treatments containing glyphosate + halauxifen-methyl + diclosulam were more effective than the other treatments. In addition, treatments with glyphosate + halauxifen-methyl + diclosulam decreased dry matter content of Conyza spp. between 87 and 93%, depending on the location, when compared to the control. The burndown treatment to Conyza spp. with glyphosate + halauxifen-methyl + diclosulam did not decrease soybean yield, and it was always higher than the untreated check.